2019
DOI: 10.1051/metal/2018106
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding of ultra low carbon steel: microstructure, mechanical properties and electrochemical study

Abstract: In the present investigation, the friction stir welding of ultra low carbon steel was carried out at different tool rotational speeds of 300 to 900 rpm in steps of 150 rpm for 30 mm/min traverse speed. The macro and microstructures were examined to identify the different areas of stir zone, thermomechanically affected zone and heat affected zone of the welded joints. Tensile strength of the welded joints was evaluated and maximum tensile strength of ∼336 MPa was obtained at 450 rpm tool rotational speed. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…[7][8][9] Rijkenberg et al 9 indicated that hole expansion capacity (HEC), that is, indicator of formability, of XPF steels are superior to high strength low alloy (HSLA) and dual-phase (DP) steels. Koley et al 10 clarified that high HEC value is of great importance for deep drawing applications in the automotive industry.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Rijkenberg et al 9 indicated that hole expansion capacity (HEC), that is, indicator of formability, of XPF steels are superior to high strength low alloy (HSLA) and dual-phase (DP) steels. Koley et al 10 clarified that high HEC value is of great importance for deep drawing applications in the automotive industry.…”
Section: Introductionmentioning
confidence: 99%